Autoresolution of Segregated and Mixed p‐n Stacks by Stereoselective Supramolecular Polymerization in Solution. Issue 44 (2nd September 2015) - Narayan, Bhawani; Bejagam, Karteek K.; Balasubramanian, Sundaram; George, Subi J.
Abstract: A "chirality driven self‐sorting" strategy is introduced for the controlled supramolecular organization of donor (D) and acceptor (A) molecules in multicomponent assemblies. The trans ‐1, 2‐bis(amido)cyclohexane ( trans ‐BAC) has been identified as a supramolecular motif with strong homochiral recognition to direct this chirality controlled assembly process of enantiomers in solution. Stereoselective supramolecular polymerization of trans ‐BAC appended naphthalene diimide monomers (NDIs) has been probed in detail by spectroscopic and mechanistic investigations. This chirality‐driven self‐sorting design of enantiomeric components also offers to realize mixed and segregated D‐A stacks by supramolecular co‐assembly of the NDI acceptors with trans ‐BAC appended dialkoxynaphthalene (DAN) donor monomers. Such an unprecedented chirality control on D‐A organization paves the way for the creation of supramolecular p‐n nanostructures with controlled molecular‐level organization. Abstract : Chiral stacking : A chirality‐driven self‐sorting strategy has been introduced for the construction of mixed and segregated donor‐acceptor supramolecular arrays in solution.